Alternate African Reality: Electronic, Electroacoustic and Experimental Music from Africa and the Diaspora - Koechlin, Basile (International Library of African Music, 2020)
pages: 171-174
Keywords: African diaspora; Electronic music; Experimental Music; Electroacoustic Music; CD Review; African Music